Processing rt of grammatical colocations in learners of Spanish as a foreign language (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
A main concern in cognitive research in second language acquisition is to determine how the L2 is processed in real time. This study presents the results of an experiment that analyzes processing rt (reaction time) of grammatical collocations in anglophone learners and native speakers (NS) of Spanish. The objective was to examine whether those units (e.g. reírse de) tend to be processed more rapidly than their non-collocational counterparts (e.g. reírse a). The results suggest that the collocational attribute favors processing speed in both groups, and that it tends to be more analytical in learners. These findings underscore the importance of grammatical collocation teaching and support their psychological validation.
Keywords: Grammatical collocations; processing rt; Spanish as a foreign language; anglophone learners; phraseological units